Analisis Laporan Keuangan Dalam Mengukur Kinerja Keuangan Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia - Rahmiati, Rahmiati; Nurlina, Nurlina; Amelia Rezki Septiani Amin (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze financial statements in measuring the financial performance of manufacturing companies in the basic industry and chemical sector listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. Financial statements were analyzed using financial ratios, including liquidity, solvency ratios, and profitability ratios. This research employed a descriptive quantitative method with a purposive sampling technique, resulting in 11 companies selected as the sample. The data were obtained from the companies' annual financial reports published on the official IDX website. The results of the study indicate that most companies in the basic industry and chemical sector have varied financial performance, with several companies achieving good liquidity, solvency, and profitability ratios according to industry standards, while others still face challenges in maintaining financial health. This analysis is expected to serve as a reference for internal and external stakeholders in making economic decisions.